Every light has its shadow: a longitudinal study of transformational leadership and leaders' emotional exhaustion. Issue 1 (9th October 2015) - Zwingmann, Ina; Wolf, Sandra; Richter, Peter
Abstract: This study investigated the effects of transformational and laissez‐faire leadership on leaders' own emotional exhaustion over time. Participants were 2, 324 subordinates and 76 supervisors of a services company in Germany. Regression analysis revealed direct longitudinal health‐hampering effects of transformational and laissez‐faire leadership on leaders' emotional exhaustion. Building on Hobfoll's Conservation of Resources theory (1989), our results showed that the longitudinal health‐hampering effects of transformational leadership would be particularly pronounced for leaders with high levels of organization‐based self‐esteem. Our findings extend the research on potential dark sides of transformational and laissez‐faire leadership as well as organization‐based self‐esteem by focusing on leader‐centered outcomes.